Beban Ganda Zakat Profesi dan Pajak Penghasilan Pekerja Muslim di Samarinda - Nuryadin, Muhammad Birusman; Iswadi, Muhammad (FENOMENA, 2016)
Zakat is Islam religion obligation charged to every muslim who are capable in economic condition. A Muslim who has been adult and has a work and gets income more than life need cost and zakat limit must perform Islam religion obligation, that is a profession zakat. A Tax is collected by a state according to law against domestic and foreign citizen who live in that state. A nature of tax is a force, therefore if tax is not obeyed and it is not paid, a people who is an object of tax will be punished by the state, that punishment can be in the form of fine, property seizure or jail. The tax charged to every adult who has a work or income is called personal income tax article 21. It can be concluded that every muslim who has been adult and has a work or income more than life need cost and the zakat limit are charged with two burdens, those are personal income tax article 21 and profession zakat. There is a different idea about zakat and tax. Some one says if a person has paid personal income tax sincerely, so his profession zakat has been performed. The other one says that both tax and zakat must be paid together. The law of zakat was made for a solution of the different idea where paying zakat can lessen a calculation of the personal income tax. It is known from a result of research that performing of zakat law could not be done well, this is caused by some constraints. Finally the muslims work in Samarinda city are charged double burdens on their income, those are profession zakat and personal income tax.